Efficient 23S positronium production by stimulated decay from the 33P level - Antonello, Maddalena; Belov, A.; Bonomi, G.; Brusa, R. S.; Caccia, M.; Camper, A.; Caravita, R.; Castelli, F.; Cerchiari, G.; Comparat, D.; Consolati, G.; Demetrio, Andrea; et al. (Physical review, 2019)
We investigate experimentally the possibility of enhancing the production of 23S positronium atoms by driving the 13S-33P and 33P-23S transitions, overcoming the natural branching ratio limitation of spontaneous decay from 33P to 23S. The decay of 33P positronium atoms toward the 23S level has been efficiently stimulated by a 1312.2 nm broadband IR laser pulse. The dependence of the stimulating transition efficiency on the intensity of the IR pulse has been measured to find the optimal enhancement conditions. A maximum relative increase of ×(3.1±1.0) in the 23S production efficiency, with respect to the case in which only spontaneous decay is present, was obtained.